Pendampingan Pembudidaya dalam Monitoring Kesehatan Udang Vaname Berbasis Sistem Digital Menggunakan Aplikasi JALA - Setyono, Bagus Dwi Hari; Affandi, Rangga Idris; Palupi, Retno; Kaswadi, Hendri; Sumsanto, Muhammad; Diniariwisan, Damai; Rahmadani, Thoy Batun Citra; Diamahesa, Wastu Ayu; Fitria, Syawalina; Abidin, Zaenal (Universitas Mataram, 2025)
This community service activity aims to improve the efficiency and sustainability of whiteleg shrimp farming in Akar-akar Village, Bayan District, North Lombok Regency, through the application of digital technology. By involving the Akar-akar Utara shrimp farmer group, this program focuses on improving digital literacy of farmers and implementing the JALA application, which provides water quality monitoring, data analysis, and algorithm-based recommendations. The training results showed an increase in digital literacy of farmers from 30% to 85%. The use of this technology has proven effective in reducing shrimp mortality by 20%, increasing average harvest yields by 18%, and saving 10% on feed costs. In addition, the application of technology has also succeeded in reducing the risk of disease outbreaks, with no reports of white spot syndrome cases in pilot ponds. This program also improves operational efficiency, with pond monitoring time reduced from 4 hours to 1.5 hours per day. Although there are infrastructure constraints such as limited internet network, adaptive solutions through manual recording synchronized with the JALA application enable the sustainability of the program. Through collaboration between farmers, government, and the private sector, this program has a positive impact on increasing the productivity and welfare of farmers, and can be a model for the development of a sustainable aquaculture sector in Indonesia, supporting the achievement of sustainable development goals (SDGs).